Collaborative online international learning (COIL): an engaging strategy for narrowing learning distances between two continents - Cardoso, Catarina; Duarte, Clara C. [UNESP]; Silva, Erick J.R. [UNESP]; Fardilha, Margarida (De Gruyter, 2024)
Objectives: Internationalization is a gold standard of higher education institutions ensuring students’ contact with different environments, including different languages and different cultures. Recently, a universal model has emerged: the Collaborative Online International Learning (COIL), a teaching/learning example of internationalization at home highly driven by the COVID-19 pandemic that boosted online interactions. COIL aims to develop intercultural consciousness and collaborative learning environments among students and faculty from different countries. Methods: Here we describe and analyze a COIL experience developed between two countries, Portugal and Brazil, in the Biomedical Sciences field with the active participation of approximately 100 undergraduate students. The pedagogical experience was evaluated through different methods including students’ questionnaires which contained qualitative and quantitative evaluations. Results: Overall, 84.2 % of students rated the COIL experience with the first and second highest ratings (4 and 5, on a 1 to 5 scale), indicating a high overall satisfaction level. Conclusions: Students considered that there was a mutual exchange and development of new knowledge and acquisition of group work skills despite the time-zone difference.
Keywords: biochemistry; Collaborative Online International Learning (COIL); internationalization at home; pedagogical innovation; pharmacology